Surface free energy analysis for bipolar pulsed argon plasma treated polymer films - (:unkn) unknown (Institute of Physics Publishing, 2010)
The effect of low energy (300 eV) argon plasma treatment on the morphology of polycarbonate was studied by means of contact angle measurement, X-ray photoelectron spectroscopy (XPS), Vickers' micro hardness indentation and atomic force microscopy (AFM). The surface free energy (SFE) changes from 38.5 mJ/m2 to 74.9 mJ/m2 on increasing the treatment time and the corresponding contact angle was changed from 63° to 17°, which shows the enhancement in surface adhesion. The XPS analysis shows the increase of the C-O and C=O functional groups upon treatment. The Vickers' micro hardness was studied in the load range 10-500 gf. The micro hardness of the film increases with the treatment time. Atomic force microscopy (AFM) reveals that average surface roughness increases from 7.0 nm to 27.2 nm as treatment time increases. © 2010 IOP Publishing Ltd.